Half a Life-Time Ago - Gaskell, Elizabeth Cleghorn, 1810-1865 (Salt Lake City, UT : Project Gutenberg, 2001)
"Half a Life-Time Ago" by Elizabeth Cleghorn Gaskell is a historical novel likely written during the mid-19th century, a period known for its rich literary contributions in England. The narrative centers on the themes of love, loss, and familial obligation, providing insight into the rural life of Westmoreland and the struggles faced by its inhabitants. The story follows the life of Susan Dixon, a strong-willed woman grappling with her past and her responsibilities after the early death of her parents and the subsequent challenges she faces caring for her mentally impaired brother, Will. The novel intricately weaves together Susan's past and present, illuminating her relationship with Michael Hurst, her childhood love who ultimately drifts away due to circumstances and personal choices. The narrative depicts a series of trials that Susan endures, from her mother's death and the burden of caring for her brother to the emotional fallout from Michael's choices leading to his decline. As she strives to honor her mother's dying wish to protect Will, Susan's strength and resilience are tested time and again. The story culminates in a poignant exploration of companionship and forgiveness when Susan confronts Michael in his moment of crisis, unveiling a transformative resolution to her life's burdens as she embraces the opportunity for new beginnings amidst life's enduring challenges. (This is an automatically generated summary.)
Release date is 2001-03-01
David Price
Keywords: England -- Social life and customs -- 19th century -- Fiction